Pertumbuhan dan hasil cabai merah (Capsicum annuum L) pada Andisol dengan pemberian berbagai sumber pupuk organik dan jenis endomikoriza - Roki Safrianto; Syafruddin Syafruddin; Rina Sriwati (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
The Growth and Yield of Chili Peppers (Capsicum annuum L) on Andisol Using Various Organic Fertilizers and EndomycorrhizaeABSTRACT. This research aims to understand the effects of various organic fertilizers and endomychorrizae on the growth and yield of chili peppers on Andisol. This research uses a Randomized Block Design (RBD) of a 4 x 4 factorial design with three repetitions. The tested factors were: Organic Fertilizers, consisting of four levels, namely: O0: Without organic fertilizers, O1: Cow manure fertilizer, O2: Chicken manure fertilizer and O3: guano fertilizer, and Endomycorrhizae, consisting of four levels, namely: M0: Without endomycorrhizae, M1: Gigaspora fungi, M2: Glomus fungi, and M3: mixture of Gigaspora and Glomus fungi. This research was conducted at the Green House of Service Technical Implementation Unit (UPTD) of the Saree Horticulture Seed Center, LembahSeulawah District, Aceh Besar Regency, as well as the laboratories of Soil Science and Plant Pathology of the Faculty of Agriculture of Syiah Kuala University. The study was conducted from May to December 2013. The type of organic fertilizers used on the chili peppers affected their growth and yield. Chicken manure fertilizer improved their growth and yield better compared to those derived from cow manure and guano. The use of endomycorrhizae also affected the growth and yield of the chili peppers on Andisol. There were no differences between the two types of endomycorrhizae in regards to the growth or yield of the chili peppers.